Antidiabetic activity in vitro and in vivo of BDB, a selective inhibitor of protein tyrosine phosphatase 1B, from Rhodomela confervoides. (30th August 2020) - Luo, Jiao; Zheng, Meiling; Jiang, Bo; Li, Chao; Guo, Shuju; Wang, Lijun; Li, Xiangqian; Yu, Rilei; Shi, Dayong
Abstract : Background and Purpose: Protein tyrosine phosphatase (PTP) 1B (PTP1B) plays a critical role in the regulation of obesity, Type 2 diabetes mellitus and other metabolic diseases. However, drug candidates exhibiting PTP1B selectivity and oral bioavailability are currently lacking. Here, the enzyme inhibitory characteristics and pharmacological benefits of 3‐bromo‐4, 5‐bis(2, 3‐dibromo‐4, 5‐dihydroxybenzyl)‐1, 2‐benzenediol (BDB) were investigated in vitro and in vivo. Experimental Approach: Surface plasmon resonance (SPR) assay was performed to validate the direct binding of BDB to PTP1B, and Lineweaver–Burk analysis of the enzyme kinetics was used to characterise the inhibition by BDB. Both in vitro enzyme‐inhibition assays and SPR experiments were also conducted to study the selectivity exhibited by BDB towards four other PTP‐family proteins: TC‐PTP, SHP‐1, SHP‐2, and LAR. C2C12 myotubes were used to evaluate cellular permeability to BDB. Effects of BDB on insulin signalling, hypoglycaemia and hypolipidaemia were investigated in diabetic BKS db mice, after oral gavage. The beneficial effects of BDB on pancreatic islets were examined based on insulin and/or glucagon staining. Key Results: BDB acted as a competitive inhibitor of PTP1B and demonstrated high selectivity for PTP1B among the tested PTP‐family proteins. Moreover, BDB was cell‐permeable and enhanced insulin signalling in C2C12 myotubes. Lastly, oral administration of BDB produced effective antidiabetic effects in spontaneously diabetic mice and markedly improved islet architecture, which was coupled with an increase in the ratio of β‐cells to α‐cells. Conclusion and Implications: BDB application offers a potentially practical pharmacological approach for treating Type 2 diabetes mellitus by selectively inhibiting PTP1B.